Parliamentary oversight of the Federal Public Service Council - Asst. Lecturer. Walaa Hussein Khazzar; Assistant Professor Dr. Iyad Dawood Kweez (The college of law and political science journal, 2023)
The Federal Public Service Council is one of the bodies established by the constitution of the Republic of Iraq in force in order to organize the affairs of the public office in the state, and given the discretion that this council enjoys in matters of appointment, reappointment and promotion, so it was necessary to subject its work to political oversight represented by parliamentary oversight  In order to achieve a kind of balance between the requirements of the public interest on the one hand, and the rights of individuals on the other hand, given that Parliament is the expression of the will of the people, so it monitors the work of the executive authority, including independent bodies, including the Federal Public Service Council.      The means of parliamentary oversight on the Federal Public Service Council vary between the means mentioned in the constitutional textsAnd others mentioned in the legal texts represented by the question and the investigation as well as the interrogation.